Transition to career for students with disability: lecturers’ readiness - Ahmad, Syazwani; Khairuddin, Khairul Farhah (Institute of Advanced Engineering and Science, 2025)
Career transition is a process of transition from school education to adulthood that involves various processes of needs, skills and knowledge to prepare students with disabilities to enter the world of work. However, the career transition program is not new, but there are still a few lecturers who do not understand the implementation of the program and lack preparation and knowledge in the management of the transition program. This study explores the readiness of lecturers in the implementation of career transition for students with special needs. A semi-structured interview session was conducted with six northern community college participants under the management of the special education department. Findings show that various factors influence the implementation of career transition management for students with disabilities. The knowledge of lecturers in managing career transition programs is still lacking. In addition, there are challenges in collaboration with stakeholders to understand the importance of the career transition of students with disabilities for future marketability. Finally, this study provides significant findings that need to be followed and used as reference material by other researchers in the future.